Education for the Embodied Human : A Contemporary Understanding on Human Nature for Holistic Education - Singh, Akhil K., (Educational Research E-Books Online, Collection 2025., 2025)
Explore Education for the Embodied Human by Akhil K. Singh, where he addresses pivotal questions about human nature and education. This book examines how assumptions about human nature influence educational concepts, formulates a comprehensive, evidence-based theory of human nature, and delves into embodied cognition, backed by the latest empirical findings in cognitive science. Are you ready to challenge and transform conventional teaching through an innovative "inside-out and outside-in" approach? This essential read is perfect for educators and policymakers eager to adopt a holistic, evidence-based approach to learning. Dive into a transformative journey that reshapes education through an embodied lens.